African Metaphysics and Praxis: Revisiting the Idea of Human Development in Yoruba Metaphysical Notion of Omoluabi - Lawal, Ademola Lukman (Àgídìgbo: ABUAD Journal of the Humanities, 2024)
The discourse on African metaphysics as it relates to human development is centered around the notion of personhood predominantly extractable from the layers of oral and written traditions across African cultural worldviews. This research aims to critically evaluate the idea of African metaphysics in the light of inquiries surrounding the meaning and nature of human development, through an interrogation of the concept of person and personhood, expressed within the subsets of African socio-cultural conceptualisations, particularly the Yoruba notion of Omoluabi, which will form a crucial layer of engagement for this research. Basically, while (on the one hand); the tendency to see a generic theory of human personality or personhood as tenable everywhere would create a clash of realities in different climes and cultures, (on the other) the differences from culture to culture are perceived dialogically as handed on through stories and histories of human development from birth until death. To this end, this research will interrogate the concept of human development on the basis of how socialisation processes specifically seen through the agencies of local folklores and folktales, customs and traditions tend to interact with, influence as well as impact upon the individual view of self and the other as it relates to the conception of personality, and its succeeding roles within the community. Keywords: Africa, Metaphysics, Communitarianism, Personhood, Human Development.